Annual Report of Congressional Research Service of the Library of Congress for Fiscal Year 2016 (Congressional Research Service (CRS), 2017)
Báo cáo thường niên về dịch vụ nghiên cứu Quốc hội cho năm tài chính 2016 của Hoa Kỳ